2020
DOI: 10.1002/ange.202010202
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Solvent‐Free Catalytic C−H Methylation

Abstract: The mechanochemical, solvent‐free, highly regioselective, rhodium‐catalyzed C−H methylation of (hetero)arenes is reported. The reaction shows excellent functional‐group compatibility and is demonstrated to work for the late‐stage C−H methylation of biologically active compounds. The method requires no external heating and benefits from considerably shorter reaction times than previous solution‐based C−H methylation protocols. Additionally, the mechanochemical approach is shown to enable the efficient synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 158 publications
0
8
0
Order By: Relevance
“…1-(Pyrimidin-2-yl)-1 H -indoles were treated with MeB(OH) 2 as the methyl source in the presence of [Cp*RhCl 2 ] 2 as the catalyst and Ag 2 CO 3 as an oxidant in a stainless steel (SS) milling vessel equipped with a single SS ball using a mixer mill (MM) with the ability to oscillate at frequencies up to 36 Hz and gave 2-methyl-1-(pyrimidin-2-yl)-1 H -indoles in 72–99% yields (Scheme 33 ). 74 This process proceeds through a five-membered rhodacycle. This mechanochemical process involves shorter reaction times, no solvent, and no external heating.…”
Section: Directed C–h Functionalization Of Indolesmentioning
confidence: 99%
See 1 more Smart Citation
“…1-(Pyrimidin-2-yl)-1 H -indoles were treated with MeB(OH) 2 as the methyl source in the presence of [Cp*RhCl 2 ] 2 as the catalyst and Ag 2 CO 3 as an oxidant in a stainless steel (SS) milling vessel equipped with a single SS ball using a mixer mill (MM) with the ability to oscillate at frequencies up to 36 Hz and gave 2-methyl-1-(pyrimidin-2-yl)-1 H -indoles in 72–99% yields (Scheme 33 ). 74 This process proceeds through a five-membered rhodacycle. This mechanochemical process involves shorter reaction times, no solvent, and no external heating.…”
Section: Directed C–h Functionalization Of Indolesmentioning
confidence: 99%
“…Indoline was activated at both C2–H and C7–H by the varying frequency of the mixer mill (MM) (Scheme 34 ). 74 Reaction of 1-(pyrimidin-2-yl)indoline with MeBF 3 K, [Cp*RhCl 2 ] 2 , AgSbF 6 , and Ag 2 CO 3 at 25 Hz resulted in 7-methyl-1-(pyrimidin-2-yl)indoline with no dimethylation, while reaction at 36 Hz gave 2,7-dimethyl-1-(pyrimidin-2-yl)-1 H -indole. Control experiments showed that both Ag 2 CO 3 and Me-BF 3 K are necessary to form 2,7-dimethyl-1-(pyrimidin-2-yl)-1 H -indole.…”
Section: Directed C–h Functionalization Of Indolesmentioning
confidence: 99%
“…11 The Pilarski group developed a highly regioselective mechanochemical C–H methylation of (het)arenes in the presence of a rhodium complex under solvent-free conditions. 12 This protocol requires shorter reaction times than with previous solution-based reactions, and no external heating is necessary. The Geneste group realized a hydroxylation of aryl or hetaryl fluorides by using KOH as base with the assistance of ball milling.…”
Section: Table 1 Optimization Of the Asymmetric Transfe...mentioning
confidence: 99%
“…This introduces a solvent free, lower operating temperatures and reduced reaction time strategy to afford desired protocol and also opens new mechanistic pathways to study. [42c,d] Recently in 2021, Pilarski and co‐workers [42e] successfully accomplished a Rh‐catalyzed methylation 40 of 2‐phenyl benzothiazole with methyltrifluroborate 39 a as methylating agent. Authors also enumerated the concept to other directing groups such as phenyl‐pyridine, indoline etc.…”
Section: C−c Bond Formationmentioning
confidence: 99%